Horizontal subcontracting and the global factory - Buckley, Peter J.; Murphree, Michael; Anderson, John (Journal of International Business Studies, 2024)
Abstract The focus of this article is the examination of the factors that trigger the addition of horizontal subcontracting to the structure of global factories. Horizontal subcontracting takes place when one firm is contracted to produce a given item, fills as much of the order as they are able to based on their available capacity, and subsequently subcontracts the remainder to a qualitatively identical firm. We find that similar entrepreneurial backgrounds of contract manufacturers lead to strong business ties in the same industry and stage of production; low-cost, used production machinery and inexpensive factory rent lead to low barriers to entry; tightening labor markets, limited capital access and lumpy or uncertain demand lead to the need to avoid underused internal capacity, and the widespread use of digital sourcing platforms by buyers enables contract manufacturers to receive orders both small and much larger than their internal production capacity. These factors combine to produce many networked small manufacturers who use horizontal subcontracting to ensure sustained demand. Currently a largely China-based phenomenon, horizontal subcontracting is likely to spread beyond China, offering a new source of vitality to low-cost manufacturing in global factories, keeping global factories viable into the future.